(untitled) (Journal of Applied Learning and Teaching, 2024)
This research was undertaken to find pedagogical solutions that help teachers design engaging learning activities and assessments. These solutions aim to increase student engagement, encourage them to take responsibility for their learning in practical training and education settings and effect positive classroom change. An action research methodology was utilised for the researchers to learn through action, increase student engagement, and develop professionally and personally. Action research is a family of research methodologies that pursue action (or change) and research (or understanding) simultaneously using a cyclic or spiral process that alternates between action and critical reflection. This methodology involved action, evaluation, and reflection to gather evidence to implement classroom change. The research found that adopting student-centred teaching practices, such as project-based learning and collaborative activities, has substantially improved student involvement with the learning process. The students who participated in the activities showed increased interest, motivation, and active participation in their educational experiences.